(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article presents an analysis of the stress-deformed state of thin-walled reinforced concrete shells-domes. The surfaces are outlined for similar geometric shapes. More rational form of the two possible is defined. Keywords: dome, umbellate dome, foldеd dome, PC "Lira", the Gaussian curvature, principal stresse.